Organizational innovation and its determinants: A comparative case study - Sojo-Castro, Marjorie (2017)
This research is qualitative, based on the technique of case studies. Relevant theory was consulted in order to analyze the determinants of organizational innovations in manufacturing industries of two geographical areas: an industrial corridor in Costa Rica and other one in Mexico. In depth were interviewed managers of three firms in Costa Rica, and managers of three companies in Mexico answered structured questionnaires. These interviews and questionnaires were conducted in order to meet their perceptions about factors  that may determine organizational innovation. The Atlas.ti software was used for the analysis of textual data. Eleven variables identified previously in the literature were measured in order to find out the degree of their association with the introduction of organizational innovations. Data from both countries suggest that six variables are associated positively with innovations of this kind; one is associated negatively, and two are not related to them. The remaining two are positive for Mexico, but are not related to organizational innovations in Costa Rica. According to the results, the most determinant variables are Sources of Information, Competences, and Difficulties to Innovate. On the other hand, regarding to the variables of Size and Productivity, there is no evidence that suggests an association with the introduction of organizational innovations.